2012
DOI: 10.1007/s11136-012-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding older patients’ self-management abilities: functional loss, self-management, and well-being

Abstract: PurposeThis study aimed to increase our understanding of self-management abilities and identify better self-managers among older individuals.MethodsOur cross-sectional research was based on a pilot study of older people who had recently been admitted to a hospital. In the pilot study, all patients (>65 years of age) who were admitted to the Vlietland hospital between June and October 2010 were asked to participate, which led to the inclusion of 456 older patients at baseline. A total of 296 patients (65% respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 38 publications
2
64
2
1
Order By: Relevance
“…In this study, the higher the age and the lower the income, the higher the SASCC score. Nevertheless, previous studies conducted in socioeconomic contexts that differed from the one in this study showed that younger ages and higher incomes were associated with higher scores in self-care agency assessment (1)(2)8,19) . A study conducted in Turkey among individuals with chronic obstructive pulmonary disease pointed to an association between higher ages and lower purchasing power and worse self-care agency (1) .…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In this study, the higher the age and the lower the income, the higher the SASCC score. Nevertheless, previous studies conducted in socioeconomic contexts that differed from the one in this study showed that younger ages and higher incomes were associated with higher scores in self-care agency assessment (1)(2)8,19) . A study conducted in Turkey among individuals with chronic obstructive pulmonary disease pointed to an association between higher ages and lower purchasing power and worse self-care agency (1) .…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, there might be a relation between the self-care agency maintenance and development, an ability that is learned throughout life, with the subsequent demands of the health-illness process (1)(2)17,19) . In this scenario, it is worth underscoring the Self-care Deficit Nursing Theory for fostering maintenance and development of self-care practices, enhancing quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are two main ways to measure EQ: trait EQ, which measures self-perception of emotional factors; and ability EQ, which measures more cognitively based EQ through maximal performance tests (14). Investigating trait EQ is especially pertinent in this population because of the strong relationship between emotional factors and COPD-related well-being and self-management abilities (15)(16)(17)(18)(19). Importantly, EQ is a trainable skill that has been used extensively in corporate business (20) to improve well-being and performance.…”
mentioning
confidence: 99%